Xanthophyll nano-particles based on electrostatic self-assembly and preparation method of xanthophyll nano-particles

By encapsulating lutein in nanoparticles through electrostatic self-assembly of polyglutamic acid and chitosan oligosaccharides, the problems of poor stability and solubility of lutein during food processing and storage have been solved, enabling its wide application in pigments, food, pharmaceuticals and feed.

CN120814644AInactive Publication Date: 2025-10-21TIANJIN BEIYANG BAICHUAN BIOTECHNOLOGY CO LTD

Patent Information

Application Number
CN202511243664.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-02
Publication Date
2025-10-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Lutein is susceptible to external environmental influences during food processing, storage, and application, resulting in poor stability and solubility, as well as low bioavailability, which limits its application in the food and pharmaceutical fields.

Method used

Lutein was encapsulated in nanoparticles formed by electrostatic self-assembly of polyglutamic acid and chitosan oligosaccharide. The resulting nanoparticles had a diameter of 180–250 nm and an encapsulation rate of 60–90%.

Benefits of technology

It improves the water solubility, thermal stability and storage stability of lutein, enhances its antioxidant capacity, and is suitable for industries such as pigments, food, pharmaceuticals and feed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120814644A_ABST
    Figure CN120814644A_ABST
Patent Text Reader

Abstract

The invention provides a xanthophyll nano-particle based on electrostatic self-assembly, which is formed by electrostatic self-assembly and spontaneous aggregation of polyglutamic acid and chitosan oligosaccharide and embedding of xanthophyll at the same time. The mass ratio of the polyglutamic acid to the chitosan oligosaccharide to the xanthophyll is 4: 600: 3; the particle size of the xanthophyll nanoparticles is 180-250 nm, and the encapsulation efficiency of the xanthophyll nanoparticles is 60-90%; the preparation process comprises the following steps: mixing a polyglutamic acid aqueous solution and a xanthophyll anhydrous alcohol solution, and fully mixing and stirring for later use; dropwise adding the mixed solution into the chitosan oligosaccharide aqueous solution, and fully stirring and mixing to obtain a xanthophyll nanoparticle solution; and removing insoluble xanthophyll, and freeze-drying to obtain the xanthophyll composite nanoparticles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lutein processing, and particularly relates to a method for nano-encapsulating lutein based on the principle of electrostatic self-assembly. Background Art

[0002] Lutein (Lutein, Lut) belongs to the carotenoid family and is one of the nutrients necessary for physiological health. Lutein is a natural pigment widely found in vegetables and fruits. Its structure contains many unsaturated double bonds, which gives it excellent antioxidant properties. In addition, its key role in improving cognition, treating macular diseases caused by aging, and alleviating cardiovascular diseases has gradually become prominent. As a member of the carotenoid family, lutein is beneficial for preventing and alleviating various eye diseases and symptoms, such as reducing the risk of cataracts or age-related macular degeneration, preventing cancer and immune regulation. Since the key enzymes for lutein biosynthesis do not exist in the human body, the main way to ingest lutein is through vegetables, fruits and lutein dietary supplements.

[0003] Even though lutein has numerous biologically active functions, in the food development process, due to the long hydrocarbon chain and conjugated double bonds in its chemical structure, its chemical properties are unstable and it is sensitive to factors such as oxygen, temperature, pH and light. Therefore, it is easy to cause loss of biological activity and product quality during food processing, storage, transportation and application. At the same time, like most hydrophobic bioactive substances, lutein is insoluble in water and can be dissolved in organic solvents such as ethanol and ethyl acetate. It also has low bioavailability, which greatly limits its application in fields such as food processing and medicine. Therefore, there are fewer natural lutein products on the market, and most of them are lutein ester-related products, such as lutein ester tablets and lutein ester soft capsules. However, there are significant differences between lutein esters and natural lutein in terms of structure, stability, functionality, bioavailability, etc. In summary, how to maintain the stability of natural lutein under processing conditions and improve its solubility have become important scientific issues that need to be addressed in the basic theoretical research on the development of lutein-rich foods.

[0004] Research reports indicate that delivery systems such as nanoparticles, liposomes, microcapsules, and emulsions can improve lutein's water solubility, enhance its stability, and control its delivery and release, thereby increasing its bioavailability. Nanoparticles, by encapsulating bioactive ingredients within synthetic or natural polymer macromolecules, can significantly enhance the bioavailability of lipid-soluble compounds with low bioavailability. Nanoparticles offer the advantages of small size, excellent stability, and high loading capacity, effectively improving lutein's stability during production, transportation, and storage. For example, Chinese patent CN 116059386A synthesizes a graft copolymer with polyacrylic acid as the backbone and lutein as the side chains by reacting lutein with polyacrylates. The graft copolymer then self-assembles in water and loads unreacted lutein to form composite nanoparticles. However, this method involves multiple reactions, the use of organic solvents, and toxic chemicals, making it environmentally unfriendly. Chinese patent CN 116391864A produces protein-based lutein nanoparticles by adjusting the pH of a protein dispersion and mixing it with a lutein-anhydrous ethanol solution. The prepared lutein nanoparticles significantly improve the water solubility, thermal stability, photostability and bioavailability of lutein.

[0005] At present, there are no reports on the preparation of composite nanoparticles using electrostatic self-assembly of polyglutamic acid and chitosan oligosaccharides and their use as carriers of bioactive ingredients. Summary of the Invention

[0006] The present invention aims to address the instability and low bioavailability of lutein by providing lutein nanoparticles based on the principle of electrostatic self-assembly and a method for preparing the same. The method utilizes polyglutamic acid and chitosan oligosaccharides to form lutein-encapsulated nanoparticles through electrostatic self-assembly. This method is simple to operate, requires mild conditions, is environmentally friendly, and has excellent biocompatibility. The resulting lutein nanoparticles have improved water solubility, thermal stability, storage stability, and antioxidant capacity.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] The present invention provides electrostatically self-assembled lutein nanoparticles. The lutein nanoparticles are formed by spontaneously aggregating polyglutamic acid and chitosan oligosaccharides, while simultaneously encapsulating lutein to form nanoparticles. The mass ratio of polyglutamic acid to chitosan oligosaccharides to lutein is 4:600:3. The lutein nanoparticles have a particle size of 180 to 250 nm and an encapsulation efficiency of 60 to 90%. The lutein nanoparticle preparation method comprises the following steps: mixing a polyglutamic acid aqueous solution with a lutein anhydrous alcohol solution, thoroughly mixing and stirring for standby use; dropwise adding the mixed solution to the chitosan oligosaccharide aqueous solution, thoroughly stirring and mixing to obtain a lutein nanoparticle solution; and removing insoluble lutein from the lutein nanoparticle solution, followed by freeze-drying to obtain lutein composite nanoparticles.

[0009] The present invention also provides a method for preparing the above-mentioned lutein nanoparticles by electrostatic self-assembly, which comprises the following steps:

[0010] (1) dissolving polyglutamic acid with a molecular weight of 10 kd to 1000 kd in water to obtain a polyglutamic acid aqueous solution with a mass volume concentration of 0.04% to 0.4%; dissolving lutein in anhydrous ethanol to obtain a lutein solution with a mass volume concentration of 0.002% to 0.024%;

[0011] (2) Mixing the polyglutamic acid aqueous solution with the lutein solution in a ratio of 1:1 to 1:6, stirring at a temperature of 20-60° C. at a speed of 200-1500 rpm / min; reacting for 10-120 min, and setting aside;

[0012] (3) The polyglutamic acid and lutein mixed solution after the reaction is added dropwise to a 0.1% to 0.8% chitosan oligosaccharide aqueous solution at a volume ratio of 1:2 to 1:10, at a temperature of 20-60°C, a stirring speed of 200 to 1500 rpm / min; the reaction time is 10 to 120 minutes, and the stirring reaction is carried out for 10 to 120 minutes to obtain a lutein nanoparticle solution.

[0013] (4) The lutein nanoparticle solution is free of insoluble lutein and then freeze-dried to obtain lutein composite nanoparticles.

[0014] Furthermore, the polyglutamic acid in step (1) preferably has a molecular weight of 10 kd to 500 kd, and more preferably has a molecular weight of 30 kd to 250 kd.

[0015] Furthermore, the mass volume concentration of the polyglutamic acid aqueous solution in step (1) is preferably 0.04% to 0.2%, more preferably, the mass volume concentration of the polyglutamic acid solution is 0.06% to 0.08%;

[0016] Preferably, the mass volume concentration of the lutein alcohol solution is 0.002008% to 0.024%, and more preferably, the concentration of the lutein alcohol solution is 0.016% to 0.02%.

[0017] Furthermore, in step (2), the volume ratio of the polyglutamic acid to the lutein solution is 1:2 to 1:5, and more preferably, the volume ratio of the polyglutamic acid to the lutein solution is 1:3.

[0018] Furthermore, in step (2), preferably, the reaction temperature is 20-40° C.; the stirring speed is 200-800 rpm / min; and the reaction time is 30-60 min.

[0019] Furthermore, the concentration of the chitosan oligosaccharide solution in step (3) is preferably 0.4% to 0.8%.

[0020] Furthermore, the volume ratio of the polyglutamic acid / lutein mixed solution to the chitosan oligosaccharide solution in step (3) is preferably 1:4 to 1:6.

[0021] Furthermore, the reaction temperature in step (3) is 20-60°C; the stirring speed is 200-1500 rpm / min; and the reaction time is 10-120 min. Preferably, the reaction temperature is 20-40°C; the stirring speed is 200-800 rpm / min; and the reaction time is 30-60 min.

[0022] A preferred preparation process is as follows: (1) dissolving polyglutamic acid with a molecular weight of 30 kd in water at a concentration of 0.08% (w / v) and a pH of 6.0; dissolving lutein in anhydrous ethanol solution at a concentration of 0.02% (w / v); adding the polyglutamic acid aqueous solution to the lutein alcohol solution at a volume ratio of 1:3, and magnetically stirring at a speed of 400 rpm / min at 25°C for 10 minutes; (2) adding the polyglutamic acid and lutein mixed solution in the above step (1) dropwise at a volume ratio of 1:5 to a chitosan oligosaccharide solution at a concentration of 0.6% (w / v) and a pH of 5.2 at a speed of 1 ml / min, and continuously stirring at a speed of 600 rpm / min at 25°C for 60 minutes; (3) removing insoluble lutein from the prepared composite solution and vacuum freeze-drying it to obtain lutein-loaded nanoparticles.

[0023] The lutein nanoparticles prepared by the method of self-assembly of polyglutamic acid and chitosan oligosaccharide to nano-encapsulate lutein provided by the present invention have a wide range of applications in the preparation of products, including: (1) pigments, which can be used as pigments in the production of cakes, candies and other foods to give them an orange appearance; (2) foods, which can be directly used as dietary supplements or as auxiliary materials to produce lutein-fortified foods such as functional beverages; (3) medicines, which can be used as auxiliary materials to produce medicines for relieving eye fatigue; and (4) feed, which can be used as chicken feed to enrich eggs with lutein.

[0024] The technical solution principle and beneficial effects of the present invention are as follows:

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The present invention proposes for the first time a method for nano-encapsulating lutein by electrostatic self-assembly of polyglutamic acid and chitosan oligosaccharide. The method involves simple equipment and steps, is safe and green, has low cost and low energy consumption, and has broad application prospects in the pigment, food, medicine and feed industries.

[0027] (2) The method of self-assembly of polyglutamic acid and chitosan oligosaccharide nano-encapsulation of lutein proposed in the present invention is that under acidic conditions, polyglutamic acid molecules are negatively charged because the carboxylate (-COO-) in the glutamic acid residue is partially protonated under acidic conditions but still maintains negative charge, while chitosan oligosaccharide molecules are positively charged because the amino group (-NH2) is protonated to -NH3 under acidic conditions. + Electrostatic attraction drives the spontaneous aggregation of polyglutamic acid and chitosan oligosaccharide molecules, and hydrophobic interactions and hydrogen bonds further stabilize the structure, eventually forming nanoparticles, achieving efficient encapsulation of lutein, and ultimately forming lutein nanoparticles with dense structure and small size.

[0028] The method for nano-encapsulating lutein by electrostatic self-assembly of polyglutamic acid and chitosan oligosaccharide proposed in the present invention can regulate the size of the formed lutein nanoparticles by changing the concentration of polyglutamic acid and chitosan oligosaccharide.

[0029] The lutein nanoparticles prepared by the self-assembly of polyglutamic acid and chitosan oligosaccharide to nano-encapsulate lutein can improve the water solubility, thermal stability, storage stability and antioxidant capacity of lutein. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is a particle size distribution diagram of lutein nanoparticles and empty nanoparticles prepared in Example 1;

[0031] Figure 2 is the zeta potential distribution diagram of the lutein nanoparticles prepared in Example 1;

[0032] Figure 3 Graph showing the encapsulation efficiency and drug loading of lutein nanoparticles prepared using lutein solutions of different concentrations in Example 2;

[0033] Figure 4 This is a graph showing the encapsulation efficiency and drug loading of lutein nanoparticles prepared using polyglutamic acid of different molecular weights in Example 3;

[0034] Figure 5 This is a graph showing the encapsulation efficiency and drug loading of lutein nanoparticles prepared using different chitosan oligosaccharide concentrations in Example 4;

[0035] Figure 6 Graph showing the encapsulation efficiency and drug loading of lutein nanoparticles prepared using different polyglutamic acid concentrations in Example 5;

[0036] Figure 7 This is a scanning electron microscope image of the lutein nanoparticles prepared in Example 1.

[0037] Figure 8 is a transmission electron micrograph of the lutein nanoparticles prepared in Example 1;

[0038] Figure 9 This is a comparison chart of the thermal stability of the lutein nanoparticles and free lutein prepared in Example 1;

[0039] Figure 10 This is a comparison chart of the lutein retention rates of the lutein nanoparticles prepared in Example 1 and free lutein in a 30-day storage experiment;

[0040] Figure 11 30-day storage experiment of lutein nanoparticles prepared in Example 1 shows the particle size, PDI, and zeta potential of the lutein nanoparticles; DETAILED DESCRIPTION

[0041] The present invention is described more clearly and completely through the following examples, but the examples described are only part of the embodiments of the present invention, not all of them. The examples are for helping to understand the present invention and should not be used to limit the scope of protection of the present invention.

[0042] In the following examples, experimental methods without specific conditions are generally performed under conventional conditions or according to the conditions recommended by the manufacturer. Unless otherwise specified, the materials and reagents used in these examples were obtained from commercial sources.

[0043] Example 1:

[0044] The method comprises the following steps:

[0045] (1) Dissolve polyglutamic acid (30 kd) in water to a concentration of 0.08% (w / v) at a pH of 6.0. Dissolve lutein in anhydrous ethanol to a concentration of 0.02% (w / v). Add 1 ml of the polyglutamic acid solution to 4 ml of the lutein solution and stir magnetically at 400 rpm / min at 25°C for 10 min.

[0046] (2) The polyglutamic acid / lutein mixed solution was added dropwise at a rate of 1 ml / min to 20 ml of a chitosan oligosaccharide solution having a concentration of 0.6% (w / v) and a pH of 5.2, and stirred at a speed of 600 rpm / min at 25°C for 60 min.

[0047] (3) After removing insoluble lutein from the prepared composite solution, the solution was freeze-dried in vacuum for 24 h to obtain lutein-loaded nanoparticles.

[0048] Example 2:

[0049] Method 1: A method for preparing protein-based lutein nanoparticles by self-assembly of polyglutamic acid and chitosan oligosaccharide to encapsulate lutein, comprising the following steps:

[0050] (1) Dissolve polyglutamic acid (30 kd) in water to a concentration of 0.08% (w / v) at a pH of 6.0. Dissolve lutein in anhydrous ethanol to a concentration of 0.02% (w / v). Add 1 ml of the polyglutamic acid solution to 4 ml of the lutein solution and stir magnetically at 400 rpm / min at 25°C for 10 min.

[0051] The polyglutamic acid / lutein mixed solution was added dropwise at a rate of 1 ml / min to 20 ml of a chitosan oligosaccharide solution with a concentration of 0.6% (w / v) and a pH of 5.2, and stirred at 600 rpm / min at 25°C for 60 min.

[0052] The prepared composite solution was freed from insoluble lutein and then freeze-dried for 24 hours to obtain lutein-loaded nanoparticles.

[0053] Method 2: Protein-based lutein nanoparticles are prepared by self-assembly of polyglutamic acid and chitosan oligosaccharide to nano-encapsulate lutein. The preparation method is the same as method 1 in this embodiment, except that the concentration of the lutein solution in step (1) is 0.002%.

[0054] Method 3: A polyglutamic acid and chitosan oligosaccharide self-assembled nano-encapsulated lutein to prepare protein-based lutein nanoparticles. The preparation method is the same as method 1 in this embodiment, except that the concentration of the lutein solution in step (1) is 0.008%.

[0055] Method 4: A polyglutamic acid and chitosan oligosaccharide self-assembled nano-encapsulated lutein to prepare protein-based lutein nanoparticles. The preparation method is the same as method 1 in this embodiment, except that the concentration of the lutein solution in step (1) is 0.012%.

[0056] Method 5: A polyglutamic acid and chitosan oligosaccharide self-assembled nano-encapsulated lutein to prepare protein-based lutein nanoparticles. The preparation method is the same as method 1 in this embodiment, except that the concentration of the lutein solution in step (1) is 0.016%.

[0057] Method 6: Protein-based lutein nanoparticles are prepared by self-assembly of polyglutamic acid and chitosan oligosaccharide to encapsulate lutein. The preparation method is the same as method 1 in this embodiment, except that the concentration of the lutein solution in step (1) is 0.024%.

[0058] Example 3:

[0059] Method 1: A method for preparing protein-based lutein nanoparticles by self-assembly of polyglutamic acid and chitosan oligosaccharide to encapsulate lutein, comprising the following steps:

[0060] Dissolve 30kd polyglutamic acid in water to a concentration of 0.08% (w / v) at a pH of 6.0. Dissolve lutein in anhydrous ethanol to a concentration of 0.02% (w / v). Add 1 ml of the polyglutamic acid solution to 4 ml of the lutein solution and stir magnetically at 400 rpm / min at 25°C for 10 minutes.

[0061] The polyglutamic acid / lutein mixed solution was added dropwise at a rate of 1 ml / min to 20 ml of a chitosan oligosaccharide solution having a concentration of 0.6% (w / v) and a pH of 5.2, and stirred at a speed of 600 rpm / min at 25°C for 60 min.

[0062] The prepared composite solution was freed from insoluble lutein and then freeze-dried for 24 hours to obtain lutein-loaded nanoparticles.

[0063] Method 2: A protein-based lutein nanoparticle is prepared by self-assembly of polyglutamic acid and chitosan oligosaccharide to nano-encapsulate lutein. The preparation method is the same as method 1 in this embodiment, except that the molecular weight of polyglutamic acid in step (1) is 58 kd.

[0064] Method 3: A protein-based lutein nanoparticle is prepared by self-assembly of polyglutamic acid and chitosan oligosaccharide to nano-encapsulate lutein. The preparation method is the same as method 1 in this embodiment, except that the molecular weight of polyglutamic acid in step (1) is 100 kd.

[0065] Method 4: A protein-based lutein nanoparticle is prepared by self-assembly of polyglutamic acid and chitosan oligosaccharide to nano-encapsulate lutein. The preparation method is the same as method 1 in this embodiment, except that the molecular weight of the polyglutamic acid in step (1) is 150 kd.

[0066] Method 5: A method of preparing protein-based lutein nanoparticles by self-assembly of polyglutamic acid and chitosan oligosaccharide to nano-encapsulate lutein. The preparation method is the same as method 1 in this embodiment, except that the molecular weight of polyglutamic acid in step (1) is 250 kd.

[0067] Example 4:

[0068] Method 1: A method for preparing protein-based lutein nanoparticles by self-assembly of polyglutamic acid and chitosan oligosaccharide to encapsulate lutein, comprising the following steps:

[0069] Dissolve 30kd polyglutamic acid in water to a concentration of 0.08% (w / v) at a pH of 6.0. Dissolve lutein in anhydrous ethanol to a concentration of 0.02% (w / v). Add 1 ml of the polyglutamic acid solution to 4 ml of the lutein solution and stir magnetically at 400 rpm / min at 25°C for 10 minutes.

[0070] The polyglutamic acid / lutein mixed solution was added dropwise at a rate of 1 ml / min to 20 ml of a chitosan oligosaccharide solution with a concentration of 0.6% (w / v) and a pH of 5.2, and stirred at 600 rpm / min at 25°C for 60 min.

[0071] The prepared composite solution was freed from insoluble lutein and then freeze-dried for 24 hours to obtain lutein-loaded nanoparticles.

[0072] Method 2: Protein-based lutein nanoparticles were prepared by self-assembly of polyglutamic acid and chitosan oligosaccharide to encapsulate lutein. The preparation method was the same as that of method 1 in this embodiment, except that the chitosan oligosaccharide concentration was 0.1%.

[0073] Method 3: Protein-based lutein nanoparticles were prepared by self-assembly of polyglutamic acid and chitosan oligosaccharide to encapsulate lutein. The preparation method was the same as that of method 1 in this embodiment, except that the chitosan oligosaccharide concentration was 0.3%.

[0074] Method 4: Protein-based lutein nanoparticles were prepared by self-assembly of polyglutamic acid and chitosan oligosaccharide to encapsulate lutein. The preparation method was the same as that of method 1 in this embodiment, except that the chitosan oligosaccharide concentration was 0.5%.

[0075] Method 5: Protein-based lutein nanoparticles were prepared by self-assembly of polyglutamic acid and chitosan oligosaccharide to encapsulate lutein. The preparation method was the same as that of method 1 in this embodiment, except that the chitosan oligosaccharide concentration was 0.7%.

[0076] Method 6: Protein-based lutein nanoparticles were prepared by self-assembly of polyglutamic acid and chitosan oligosaccharide to encapsulate lutein. The preparation method was the same as that of method 1 in this embodiment, except that the chitosan oligosaccharide concentration was 0.8%.

[0077] Example 5:

[0078] Method 1: A method for preparing protein-based lutein nanoparticles by self-assembly of polyglutamic acid and chitosan oligosaccharide to encapsulate lutein, comprising the following steps:

[0079] Dissolve 30kd polyglutamic acid in water to a concentration of 0.08% (w / v) at a pH of 6.0. Dissolve lutein in anhydrous ethanol to a concentration of 0.02% (w / v). Add 1 ml of the polyglutamic acid solution to 4 ml of the lutein solution and stir magnetically at 400 rpm / min at 25°C for 10 minutes.

[0080] The polyglutamic acid / lutein mixed solution was added dropwise at a rate of 1 ml / min to 20 ml of a chitosan oligosaccharide solution with a concentration of 0.6% (w / v) and a pH of 5.2, and stirred at 600 rpm / min at 25°C for 60 min.

[0081] The prepared composite solution was freed from insoluble lutein and then freeze-dried for 24 hours to obtain lutein-loaded nanoparticles.

[0082] Method 2: Protein-based lutein nanoparticles are prepared by self-assembly of polyglutamic acid and chitosan oligosaccharide to nano-encapsulate lutein. The preparation method is the same as method 1 in this embodiment, except that the concentration of polyglutamic acid in step (1) is 0.004%.

[0083] Method 3: A protein-based lutein nanoparticle is prepared by self-assembly of polyglutamic acid and chitosan oligosaccharide to nano-encapsulate lutein. The preparation method is the same as method 1 in this embodiment, except that the concentration of polyglutamic acid in step (1) is 0.02%.

[0084] Method 4: A protein-based lutein nanoparticle is prepared by self-assembly of polyglutamic acid and chitosan oligosaccharide to nano-encapsulate lutein. The preparation method is the same as method 1 in this embodiment, except that the concentration of polyglutamic acid in step (1) is 0.04%.

[0085] Method 5: A method of preparing protein-based lutein nanoparticles by self-assembly of polyglutamic acid and chitosan oligosaccharide to nano-encapsulate lutein. The preparation method is the same as method 1 in this embodiment, except that the concentration of polyglutamic acid in step (1) is 0.12%.

[0086] Method 6: A method of preparing protein-based lutein nanoparticles by self-assembly of polyglutamic acid and chitosan oligosaccharide to nano-encapsulate lutein. The preparation method is the same as method 1 in this embodiment, except that the concentration of polyglutamic acid in step (1) is 0.24%.

[0087] Method 7: A protein-based lutein nanoparticle is prepared by self-assembly of polyglutamic acid and chitosan oligosaccharide to nano-encapsulate lutein. The preparation method is the same as method 1 in this embodiment, except that the concentration of polyglutamic acid in step (1) is 0.32%.

[0088] Method 8: A method of preparing protein-based lutein nanoparticles by self-assembly of polyglutamic acid and chitosan oligosaccharide to nano-encapsulate lutein. The preparation method is the same as method 1 in this embodiment, except that the concentration of polyglutamic acid in step (1) is 0.4%.

[0089] The lutein composite nanoparticles prepared in Example 1 were subjected to characterization tests:

[0090] The particle size and zeta potential of the samples were determined using a Zetasizer Nano (Malvern, UK) dynamic light scattering method. Before measurement, the samples were equilibrated at 25°C for 2 minutes. Figure 1 、 2As shown, the average particle size of the unloaded nanoparticles is 167.88±3.01nm, and the particle size of the drug-loaded nanoparticles is 212.89±9.55nm; the zeta potential of the nanoparticles is +32.56mv, and the absolute value of the zeta potential is greater than 30mv, proving that the nanoparticle system is stable.

[0091] Determination of lutein encapsulation efficiency and drug loading: Lutein solutions of different concentrations were prepared using anhydrous ethanol solution and their absorbance was measured at 445 nm. The standard curve of lutein was obtained as follows: y = 0.148x + 0.0014, R2 = 0.9993;

[0092] Encapsulation efficiency (%) = mass of entrapped lutein / mass of added lutein × 100%;

[0093] Drug loading rate (%) = mass of embedded lutein / the sum of the mass of chitosan oligosaccharide and γ-polyglutamic acid in the composite nanoparticles × 100%.

[0094] 1 ml of the nanoparticles prepared using lutein solutions of different concentrations in Example 2 was added to 3 mL of ethyl acetate (1:3; v / v) and mixed thoroughly to extract the unencapsulated free lutein. The mixture was centrifuged at 3000 × g for 5 min to separate the organic phase from the aqueous phase. The upper organic layer was placed in a UV spectrophotometer with ethyl acetate as a blank control. The absorbance was measured at 445 nm and the free lutein content was calculated according to the standard curve to determine the encapsulation efficiency and drug loading.

[0095] The results are as follows Figure 3 As shown in the figure, with the increase of lutein concentration, the encapsulation efficiency of the system first decreased and then stabilized, while the drug loading capacity showed a significant upward trend.

[0096] The encapsulation efficiency and drug loading of the nanoparticles prepared by using polyglutamic acid of different molecular weights in Example 3 were measured. Figure 4 As shown in the figure, the encapsulation efficiency decreases with increasing polyglutamic acid molecular weight, while the drug loading of nanoparticles prepared with polyglutamic acid molecular weights other than 30kd polyglutamic acid is not significantly different. This is because the larger the polyglutamic acid molecular weight, the more partially the internal carboxyl groups are shielded, the lower the density of the carboxyl groups, and the looser the nanoparticle structure formed by electrostatic interaction with chitosan oligosaccharide, which in turn reduces the encapsulation efficiency.

[0097] The encapsulation efficiency and drug loading of the nanoparticles prepared by using different concentrations of chitosan oligosaccharides in Example 4 were determined. Figure 5 As shown in the figure, with the increase of chitosan oligosaccharide concentration, the encapsulation efficiency and drug loading capacity showed an upward trend. When the concentration exceeded 0.6%, the encapsulation efficiency and drug loading capacity decreased. This may be because the nanoparticles were self-assembled by electrostatic action, and excessive chitosan oligosaccharide introduced too many positive charges, resulting in repulsion, making it impossible to form a dense structure.

[0098] The encapsulation efficiency and drug loading of the nanoparticles prepared by using different concentrations of polyglutamic acid in Example 5 were measured. Figure 6 As shown in the figure, the polyglutamic acid concentration tends to be stable when it is greater than 0.06%, and the drug loading capacity reaches the maximum at a concentration of 0.08%.

[0099] The morphology of lutein composite nanoparticles was observed using a scanning electron microscope at an accelerating voltage of 110KV. The sample preparation method was as follows: freeze-dried nanoparticles were dispersed in an aqueous solution, dropped onto a silicon wafer, air-dried, and then placed on a conductive adhesive. After gold spraying, the sample was observed under a scanning electron microscope. Figure 7 As shown in the figure, the particle size of lutein nanoparticles under scanning electron microscopy is basically consistent with the results determined by the above-mentioned DLS method, and the average particle size is about 200 nm.

[0100] Using a transmission electron microscope, a solution of lutein nanoparticles was dropped onto a copper grid covered with a carbon film and observed after natural air drying. Figure 8 As shown in the figure, the nanoparticles were spherical and uniform in size, which was consistent with the DLS analysis, which found that the average particle size was 224.48 ± 5.16 nm.

[0101] The thermal stability of lutein monomers and lutein nanoparticles with equal lutein content was determined. Fresh lutein nanoparticles and free lutein were placed at 37°C, 50°C, 70°C, and 90°C for 50 minutes. After heat treatment, the lutein retention rate was measured using a UV spectrophotometer. The results are shown in Figure 2. Figure 9 The figure shows the retention rate of free lutein and lutein nanoparticles after heat treatment at different temperatures. Compared with free Lut, lutein nanoparticles showed significantly improved thermal stability. This may be because Lut was effectively encapsulated in the nanoparticles, slowing down the decomposition of Lut at high temperatures.

[0102] Figure 9 In the table, * represents significance. Commonly used significance levels include 0.05, 0.01, and 0.001. These values ​​represent the risk of rejecting the null hypothesis. A single asterisk (*) indicates a P value less than 0.05, meaning the result is significant at the 0.05 level; two asterisks (**) indicate a P value less than 0.01, meaning the result is significant at the 0.01 level; and three asterisks (***) indicate a P value less than 0.001, meaning the result is highly significant at the 0.001 level.

[0103] The storage stability of lutein monomers and lutein nanoparticles with equal lutein content was tested. Fresh lutein nanoparticles and free lutein were stored at 25°C for 30 days, and the lutein content was measured every 5 days. The results are as follows Figure 10As shown in the results, lutein nanoparticles significantly improved the lutein retention rate after storage compared with free lutein.

[0104] The storage stability of lutein monomers and lutein nanoparticles with equal lutein content was tested. Fresh lutein nanoparticles and free lutein were stored at 25°C for 30 days, and the particle size, PDI, and zeta potential of the lutein nanoparticles were measured every 5 days. The results are as follows: Figure 11 As shown in the data, during the 30-day storage period, the PDI of the nanoparticles was below 0.4, and the absolute value of the zeta potential remained above 30 mV. These phenomena indicate that the system maintains a certain degree of stability and has a long shelf life. In addition, the particle size of the lutein nanoparticles increases slightly with the extension of storage time.

Claims

1. A lutein nanoparticle, characterized in that: The lutein nanoparticles are formed by spontaneous aggregation of polyglutamic acid and chitosan oligosaccharide, and entrapment of lutein through electrostatic self-assembly. The mass ratio of polyglutamic acid, chitosan oligosaccharide, and lutein in the lutein nanoparticles is 4:600:

3. The particle size of the lutein nanoparticles is 180-250 nm, and the encapsulation efficiency is 60-90%. The lutein nanoparticle preparation method comprises the following steps: mixing a polyglutamic acid aqueous solution and a lutein anhydrous alcohol solution, and thoroughly mixing and stirring for standby use; adding the mixed solution dropwise to the chitosan oligosaccharide aqueous solution, and thoroughly stirring and mixing to obtain a lutein nanoparticle solution; and removing insoluble lutein from the lutein nanoparticle solution, and freeze-drying to obtain lutein composite nanoparticles.

2. The method for preparing lutein nanoparticles according to claim 1, wherein: The specific steps include: (1) dissolving polyglutamic acid with a molecular weight of 10 kd to 1000 kd in water to obtain a polyglutamic acid aqueous solution with a mass volume concentration of 0.04% to 0.4%; dissolving lutein in anhydrous ethanol to obtain a lutein alcohol solution with a mass volume concentration of 0.002% to 0.024%; (2) mixing the polyglutamic acid aqueous solution and the luteinol solution in a volume ratio of 1:1 to 1:6, stirring at a temperature of 20-60° C. at a speed of 200-1500 rpm / min; reacting for 10-120 min, and setting aside; (3) The polyglutamic acid and lutein mixed solution after the reaction in step (2) is added dropwise to a 0.1% to 0.8% chitosan oligosaccharide aqueous solution at a volume ratio of 1:2 to 1:10, and stirred at a temperature of 20-60° C. and a speed of 200 to 1500 rpm / min for 10 to 120 minutes to obtain a lutein nanoparticle solution. (4) The lutein nanoparticle solution is free of insoluble lutein and then freeze-dried to obtain lutein composite nanoparticles.

3. The method for preparing the lutein nanoparticles according to claim 2, wherein: The molecular weight of the polyglutamic acid in step (1) is 30kd to 250kd.

4. The method for preparing the lutein nanoparticles according to claim 2, wherein: The mass volume concentration of the polyglutamic acid aqueous solution in step (1) is 0.06% to 0.08%.

5. The method for preparing the lutein nanoparticles according to claim 2, wherein: The mass volume concentration of the lutein alcohol solution in step (1) is 0.016% to 0.02%.

6. The method for preparing the lutein nanoparticles according to claim 2, characterized in that: In the mixed solution of polyglutamic acid and lutein in step (2), the volume ratio of the polyglutamic acid aqueous solution to the lutein ethanol solution is 1:2 to 1:

5.

7. The method for preparing the lutein nanoparticles according to claim 2, characterized in that: The reaction temperature in step (2) is 20-40° C.; the stirring speed is 200-800 rpm / min; and the reaction time is 30-60 min.

8. The method for preparing the lutein nanoparticles according to claim 2, characterized in that: The concentration of chitosan oligosaccharide in step (3) is 0.4% to 0.8%.

9. The method for preparing the lutein nanoparticles according to claim 2, wherein: The volume ratio of the mixed solution of polyglutamic acid and lutein and the chitosan oligosaccharide solution in step (3) is 1:4 to 1:

6.

10. The method for preparing the lutein nanoparticles according to claim 2, characterized in that: The preparation steps include: (1) dissolving polyglutamic acid with a molecular weight of 30 kd in water to a mass volume concentration of 0.08% and a pH of 6.0; dissolving lutein in anhydrous ethanol solution to a mass volume concentration of 0.02%; adding the polyglutamic acid aqueous solution to the lutein alcohol solution at a volume ratio of 1:3, and magnetically stirring at a speed of 400 rpm / min at 25°C for 10 minutes; (2) adding the polyglutamic acid and lutein mixed solution in the above step (1) dropwise at a volume ratio of 1:5 to a chitosan oligosaccharide solution with a mass volume concentration of 0.6% and a pH of 5.2 at a speed of 1 ml / min, and continuously stirring at a speed of 600 rpm / min at 25°C for 60 minutes; (3) removing insoluble lutein from the prepared composite solution and vacuum freeze-drying it to obtain lutein-loaded nanoparticles.

Citation Information

Patent Citations

  • Water-soluble lutein composite nanoparticles and preparation method thereof

    CN116059386A

  • Method for inducing protein to assemble nano-embedded xanthophyll through cooperation of pH and ethanol, protein-based xanthophyll nano-particles and application of protein-based xanthophyll nano-particles

    CN116391864A

Cited By

  • Self-assembled nanoparticles for reversing liver fibrosis and preparation method and application thereof

    CN122342830A